Membangun Minat Belajar PAK di Rumah: Peran Strategis Orangtua sebagai Role Model Iman - Mila Sartika; Hendro Hariyanto Siburian (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2025)
The problem in this research is the low interest in children's learning in Christian religious education of Grade 5 students at Talenta Elementary School which is caused by the students' parents not showing role models and involving children at home in carrying out activities which are the application of the values and principles of Christian religious education which have an impact on children's interest in learning in Christian religious lessons. This research uses a qualitative descriptive method with a case study method. Data was collected through direct observation and interviews with all 20 grade 5 students at Talenta Elementary School, 10 students' parents, and 2 teachers. The aim of this research is to reveal the role of parents of Grade 5 SD Talenta students at home in developing children's emotional and spiritual aspects, and to offer supporting activities for parents in increasing students' interest in learning in Christian religious education lessons. The results of the research reveal that the role of parents in increasing interest in learning Christian religious education must be to play the role as a guide, educator, facilitator, motivator and role model optimally, which can be done in the activities of reading God's word and praising God with children at home, carrying out activities with children at home (for example, activities related to discipline and homework), and story-telling rooms (spaces where children are given to talk about their daily life experiences), as well as collaborating with parents and PAK teachers in carrying out activities to increase students' interest in learning in Christian religious education. AbstrakPersoalan dalam penelitian ini adalah rendahnya minat belajar anak pada pendidikan agama Kristen peserta didik kelas 5 SD Talenta yang disebabkan orang tua peserta didik cenderung tidak menunjukkan keteladanan atau role model dan melibatkan anak di rumah dalam melakukan kegiatan yang merupakan penerapan nilai-nilai dan prinsip-prinsip pendidikan agama Kristen yang berdampak pada minat belajar anak pada pelajaran agama Kristen. Penelitian ini menggunakan metode kualitatif deskriptif dengan metode studi kasus. Data dikumpulkan melalui observasi dan wawancara langsung terhadap seluruh peserta didik kelas 5 SD Talenta berjumlah 20 orang, orang tua peserta didik 10 orang, dan 2 orang guru. Adapun tujuan penelitian ini adalah mengungkapkan peran orang tua siswa kelas 5 SD Talenta di rumah dalam mengembangkan aspek emosional dan spiritual anak, dan menawarkan kegiatan pendukung bagi orang tua dalam meningkatkan minat belajar peserta didik dalam pelajaran pendidikan agama Kristen. Hasil penelitian menunjukkan bahwa peran orangtua dalam meningkatkan minat belajar Pendidikan agama Kristen harus melakukan peran sebagai pembimbing, pendidik, fasilitator, motivator, dan role model dengan optimal yang bisa dilakukan dalam kegiatan membaca firman Tuhan dan memuji Tuhan Bersama anak di rumah, melakukan kegiatan bersama anak di rumah (misal kegiatan berkenaan kedisiplinan dan pekerjaan rumah),  dan ruang bercerita (ruang dimana anak diberi kebebasan untuk ceritan pengalaman hidupnya sehari-hari), serta melakukan kolaborasi orang tua dengan guru PAK dalam melakukan kegiatan meningkatkan minat belajar peserta didik dalam pelajaran Pendidikan agama Kristen.